The MTHFR C677T polymorphism and global DNA methylation in oral epithelial cells - Arruda,Isabela Tatiana Sales de (2013)
DNA methylation is mediated by DNA methyltransferases (DNMTs) that add a methyl group to the 5'-carbon of cytosine. The enzyme methylenetetrahydrofolate reductase (MTHFR) catalyzes the reduction of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate in the rate-limiting step of the cycle involving the methyl donor S-adenosyl-L-methionine (SAM). The MTHFR C677T polymorphism results in a thermolabile enzyme with reduced activity that is predicted to influence the DNA methylation status. In this study, we investigated the impact of the MTHFR C677T polymorphism on the global DNA methylation of oral epithelial cells obtained from 54 healthy subjects. There were no significant differences in global DNA methylation among the MTHFR CC, CT and TT genotypes (p = 0.75; Kruskal-Wallis test).